Implementasi Teknik Self Control Terhadap Kecanduan Media Sosial Siswa - Yusuf, Ahmad; Haslinda, Haslinda; Hasbahuddin, Hasbahuddin (JURKAM: Jurnal Konseling Andi Matappa, 2019)
This study aims to determine the implementation of the Self Control technique to the problem of students' Social Media addiction before and after being given treatment. This research is a quantitative approach with Pre-Experimental design with experimental design used is One-Group Pretest-Posttest Design, consisting of 18 people as the experimental sample who are class XII students in SMA 3 Pangkep 2018/2019 academic year. Data collection using scale addiction instrument gadgets and observation guidelines. Data analysis used descriptive statistical analysis and non-parametric analysis, namely the Wilcoxon Signed Ranks Test. The results of the research obtained are: 1) An overview of the implementation of Self Control techniques in Pangkep 3 High School. 2) The level of ability to reduce social media addiction of students in Pangkep 3 High School before being treated in the form of the application of Self Control techniques is in the high category and after being given treatment in the form of Self Control techniques are in the low category. 3) there is a positive effect of Self Control techniques to improve the ability to reduce student addiction to social media in SMA Negeri 3 Pangkep.